Development of A Book on Cultivating Manners for Pancasila and Citizenship Education Subjects for Class IV Elementary School Students - Sa'adah, Fatikhatus (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2024)
This study aimed to create a book that can assist kids in cultivating proper etiquette. The research employed the Research and Development (R&D) method, utilising the ADDIE model, which consisted of five stages: Analysis, Design, Development, Implementation, and Evaluation. The data was collected through interviews and questionnaires. In addition, the data was analysed using two distinct stages: the expert evaluation stage and the product trial stage. The study’s findings, derived from expert testing, demonstrated the feasibility of the courtesy book yielded percentation comprised 95% of media experts, 88% of material experts, and 92% of linguists. The user conducted trials with students and achieved outstanding results in the One to One Evaluation (96%), Small Group (94%), and Field Test (94%), respectively. These findings demonstrated that the book product designed to inculcate courteousness in fourth-grade primary school students is appropriate for implementation.